2010
DOI: 10.1007/s11248-010-9395-4
|View full text |Cite
|
Sign up to set email alerts
|

Genotype-dependent gene expression profile of the antioxidant defense system (ADS) in the liver of a GH-transgenic zebrafish model

Abstract: The aim of this study was to evaluate the effects of growth hormone (GH) overexpression on the gene expression profile of multiple components of the antioxidant defense system (ADS) of different genotypes of a GH-transgenic zebrafish (Danio rerio) model. Several ADS-related genes were analyzed by semiquantitative reverse transcription-PCR in the liver of hemizygous (HE) and homozygous (HO) transgenic zebrafish. The results showed a significant reduction in the glutamate cysteine ligase catalytic subunit (GCLC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…According to the Minimum Information for Publication of Quantitative Real Time PCR Experiments (MIQE) 46 , a RG needs to be validated and established for each species and for different physiological conditions. Our results show that although the literature has already demonstrated alterations in the metabolism of the F0104 lineage 19 , 21 , 29 35 , 38 , 47 , 48 , these animals, in comparison to non-transgenic animals, did not suffer notable variations in the expression of most of the analyzed genes.…”
Section: Discussionsupporting
confidence: 45%
“…According to the Minimum Information for Publication of Quantitative Real Time PCR Experiments (MIQE) 46 , a RG needs to be validated and established for each species and for different physiological conditions. Our results show that although the literature has already demonstrated alterations in the metabolism of the F0104 lineage 19 , 21 , 29 35 , 38 , 47 , 48 , these animals, in comparison to non-transgenic animals, did not suffer notable variations in the expression of most of the analyzed genes.…”
Section: Discussionsupporting
confidence: 45%
“…It was shown that gh -transgenic zebrafish grew faster in a shorter period than their non-transgenic full sibling controls ( Figueiredo et al, 2007 ; Rosa et al, 2010 ; Silva et al, 2015 ) and presented enhanced muscle hypertrophy when compared to non-transgenic fish ( Kuradomi et al, 2011 ). GH overexpression also impacts oxidative metabolism ( Rosa et al, 2008 , 2011 ), aging ( Rosa et al, 2010 ), reproduction ( Figueiredo et al, 2013 ), ionic balance ( Almeida et al, 2013 ), immune system ( Batista et al, 2014 ), and appetite behavior ( Dalmolin et al, 2015 ) in this gh -transgenic zebrafish line. Collectively, these findings provide evidence that the excess of circulating GH implies mandatory growth even in unfavorable conditions, resulting in higher metabolic demand.…”
Section: Introductionmentioning
confidence: 96%
“…Cataracts are a well-known effect of oxidative stress to the lens [ 7 ]. Furthermore, growth hormone transgenic fish that have a high growth rate are known to have elevated oxidative stress [ 8 , 9 , 10 , 11 ]. These studies indicate a possible involvement of redox regulation.…”
Section: Introductionmentioning
confidence: 99%